2012
DOI: 10.1007/s10948-012-2072-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Growth Speed and Magnetic Properties in Bi-2212/Ag Textured Composites

Abstract: In this paper, the magnetic properties of Bi 2 Sr 2 CaCu 2 O x /3 wt.%Ag textured composite materials prepared by a LFZ melting technique at different growth speeds (5, 15, 30 and 60mm/h) are presented. X-ray diffraction patterns showed that in all cases the Bi-2212 phase is the major one. The magnetization measurements have been carried out as a function of the magnetic field up to 10 kOe. J c values of the samples calculated using Bean's model indicate that the different growth speeds have significant effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In particular, it has been reported that samples grown at 15 mm/h using the LFZ method provides the highest grain alignment without internal cracks [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been reported that samples grown at 15 mm/h using the LFZ method provides the highest grain alignment without internal cracks [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Among other successful techniques to produce well oriented grains, the laser texturing ensures a high degree of texture at relatively high rates [7][8][9][10][11]. Besides these useful methods used in the preparation of ceramic superconductors such as the laser floating zone (LFZ) [12] and the electrically assisted laser floating zone (EALFZ) techniques [13], cation doping [14][15][16][17][18][19][20][21][22][23][24][25][26][27] or metallic additions [28][29][30] can also ensure the important improvements in the basic properties of the BSCCO system.…”
Section: Introductionmentioning
confidence: 99%